Pengembangan Media Pembelajaran Museum Digital Pada Pembelajaran Sejarah Di SMA Negeri 1 Pariaman - Rika Agus Suryani; Ridho Bayu Yefterson (Jurnal Kronologi, 2022)
This study discusses the development of digital museum learning media using power points in history learning at SMA N 1 Pariaman. Therefore, this study aims to (1) analyze the process of developing the Digital Museum media in learning Indonesian history. (2) analyze the Feasibility Test Results and Practicality of Digital Museum Media Products in Indonesian History learning. This research method is Research and Development (R&D) using the ADDIE development model according to Branch consisting of 5 stages, namely analysis, design, development, implementation, evaluation. The results of the study show that (1) the stages of developing digital museum media are as follows: (a) the analysis stage, namely analyzing the problems that exist in history learning, at this stage a needs analysis and curriculum analysis are carried out. (b) the design stage, at this stage designing a digital museum, as a historical learning medium, the steps in this stage are making a summary of the material, creating a digital museum concept, making illustrations and pictures. (c) the development stage, at this stage the aim is to produce digital museum media that is suitable for use in history learning, from the assessments carried out by material experts and media experts. The results of the assessment show that digital museums are very suitable to be used in history learning. (d) the implementation stage, at this stage a digital museum trial was conducted as a historical learning media to determine its practicality, an assessment was carried out by students and teachers. The results showed that the digital museum media was practically used as a historical learning media. (e) evaluation stage, at this stage aims to find out the lack of media to be repaired so that it is suitable for use, researchers get advice from media experts to add a back button on the 3rd slide of digital museum media so that they can return to the media start page (2) in terms of The feasibility of Digital Museum media is broadly categorized as very feasible and can help students to better understand and identify the periodization of the development of preliterate society based on the results of their culture. (3) in terms of the practicality of the Digital Museum media as a whole it is categorized as very practical.